Embalados e prontos para comer: relações de consumo e incorporação de alimentos industrializados - Pellerano, Joana A (2014)
The purpose of this dissertation is to assess the relationship between consumers and processed foods, which are so present in urban life, in a big city like São Paulo (SP). From the survey of eating habits related to this type of food with selected consumers, relations of anxiety, confidence and incorporation (Claude Fischler, 1995) when someone allows a food to enter his or her body and to be a part of his or her physical and symbolic composition were analyzed in the context of contemporary food consumption. For this purpose, the methodology allied theoretical and empirical research. As part of the theoretical research, besides Fischler (1995), the work relies primarily on Pierre Bourdieu (1983, 2007), Michel de Certeau (1994), Luce Giard (1996), Raymond Williams (2000, 2001, 2003, 2011), Contreras Hernández and Mabel Grácia-Arnaiz (2005), Jean-Pierre Poulain (2004) and Carlos Alberto Dória (2007, 2008, 2009a, 2009b, 2012). The empirical research was qualitative and involved nine São Paulo residents aged 20 to 59 years old with a monthly family income larger than 15 minimum wages, range that consumes more processed foods according to Instituto Brasileiro de Geografia e Estatística (IBGE, 2010). Semi-structured in-depth interviews were conducted individually focusing on food life history in relation to eating nowadays. At the end of this research it was possible to understand more properly how people deal with one of their basic needs: food. When processed foods come into the equation, this relationship is permeated by anxiety, misinformation, confidence and conformity regarding what is put on their plates and in their bodies